Pengaruh Gaya Kepemimpinan Demokratis dan Motivasi Kerja terhadap Kinerja Karyawan Kantor Otoritas Bandar Udara Sam Ratulangi Manado - Panggau, Sisilia Vivin; Sundari, Ocky (Jurnal Maksipreneur, 2024)
Performance is a result of the actions of employees who have completed a job within the scope of an organization or company. This research aims to examine the influence of employee performance at the Kantor Otoritas Bandar Udara Wilayah VIII Manado through democratic leadership style and work motivation. The sample used was 64 employees. The sampling technique used in this research was saturated sampling. The analysis technique used to answer the hypothesis is multiple linear regression, the processing process is assisted by the software Statistical Package for the Social Sciences (SPSS) version 23. Data collection techniques were obtained from questionnaires. Based on testing, research results show that leadership style and work motivation influence employee performance at the Kantor Otoritas Bandar Udara Wilayah VIII Manado.